2010
DOI: 10.1044/0161-1461(2010/09-0040)
|View full text |Cite
|
Sign up to set email alerts
|

Who Does What to Whom: Introduction of Referents in Children’s Storytelling From Pictures

Abstract: These results suggest that the FM measure is a useful tool for identifying whether a child has a problem with introducing referents in stories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 41 publications
(57 reference statements)
2
41
0
Order By: Relevance
“…Microstructure measures typically include measures of productivity (e.g., number of utterances or words), language complexity (e.g., sentence length), language accuracy (e.g., verb accuracy), and referring expressions to demonstrate cohesion (e.g., Cleave et al . , Fiestas and Peña , Iluz‐Cohen and Walters , Norbury and Bishop , Pearson , Schneider and Hayward , Uccelli and Paéz ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Microstructure measures typically include measures of productivity (e.g., number of utterances or words), language complexity (e.g., sentence length), language accuracy (e.g., verb accuracy), and referring expressions to demonstrate cohesion (e.g., Cleave et al . , Fiestas and Peña , Iluz‐Cohen and Walters , Norbury and Bishop , Pearson , Schneider and Hayward , Uccelli and Paéz ).…”
Section: Introductionmentioning
confidence: 99%
“…A significant number of studies (see Boudreau for a review) have consistently reported that children with SLI display significant and persistent difficulties in both macrostructure (e.g., less story information) and microstructure (e.g., lower lexical diversity and limited grammatical complexity). Furthermore, the use of the adequate referring expressions to introduce a character in the narrative is also problematic for children with SLI and they differ from TD children after the age of four years (Norbury and Bishop , Schneider and Hayward ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By telling certain stories adult can teach children about politeness, respect, and other moral values. Stories also provide children the discourse of the language skills and provide them the reality and the knowledge of the world (Schneider & Hayward, 2010). Miller et al (1997) found in their research that both Chinese family and American family used personal storytelling to teach moral and social standard as well as building children's critical analysis.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…That is, as measured in this study, anaphor overlap was not related to semantics or syntax. Given the early development o f expertise in pronoun use (Schneider & Hayward, 2010), a measure o f the degree o f reference use may not be indicative o f developmental change in school-aged children. Perera (1984) indicated that reference ties emerge early in children's writing and by 9 years of age, are used extensively.…”
Section: Implications For Future Researchmentioning
confidence: 99%